USING γ RAY-INDUCED SILVER NANOPARTICLES ON CONTROL OF CLUBROOT DISEASE OF CHINESE CABBAGE CAUSED BY PLASMODIOPHORA BRASSICAE - Anh Tu, Le Thi; Le Ha, Pham Thi (Vietnam Journal of Biotechnology, 2018)
Plasmodiophora brassicae- the casual cause of clubroot disease of plants belonging to the family Brassicaceae. This soil-borne fungus infects plants through root hairs. Diseased roots become swollen and deformed. Thus, it’s difficult for plants to absorb water and nutrients. There are some methods used to control this disease including soil fumigation, soil pH control, fungicides, surfactants applications, calcium supplementation, but the results are still restricted. Plasmodiophora brassicae was isolated, identified and artificial inoculated on the Chinese cabbage. The rate of root hair infection and gall formation depended on the spore density and growth media. The increase of the pathogen density lead to the increase of disease symptoms. Silver nanoparticles (SNPs) are widely used as an agent for antifungal treatment. The antimicrobial activity of the nanoparticles varies on the size, shape, and the function of the surface area. The γ - irradiation method to synthesize SNPs is known as a method that can be controlled the out coming sizes, shapes and size distribution of particles. The average diameter of silver nanoparticles in this research was 9.5nm. In the liquid culture and soil, SNPs exhibited a controlling effect on P. brassicae. The fungicide activity depended on the SNP concentrations and the medium; no disease symptoms were found at the SNP concentrations of 1.06 ppm in the liquid culture, and 10 and 20 ppm in soil. Results of the study also showed that the biomass and height of infected plants were much lower than those of the healthy plants. Comparing to the plants that were grown in the sterilized soil, there was not significant difference between the biomass and the height of plants exposed to pathogen and treated with SNPs.